Circumcision in boys with mild Hemophilia A - the Yogyakarta experience - Pudjo Hagung Widjajanto; Ridwan Tjandra Sugiarto; Sutaryo Sutaryo; Kaiser Ali (Indonesian Pediatric Society Publishing House, 2007)
Background In boys with hemophilia, there is a risk of hemorrhage resulting from circumcision. There has been no standardised management in Indonesia. We report our experience with 4 hemophiliac boys who underwent circumcision at Dr. Sardjito General Hospital, Yogyakarta, in south-central Java. Objective To develop a safe, practical and accessible method to prevent bleeding in boys with hemophilia undergoing circumcision in Indonesia. Methods Written informed consent was obtained from parents requesting the procedure. All boys had mild Hemophilia A (VIII: C level >7.8 U/ml) diagnosed at a median age of 4.4 years (range 0.75-9 years). Median age at time of circumcision was 7.5 years (range 0.8-12 years). Results There were no intraoperative or post-circumcision bleeding problem encountered in any of the patients, who were discharged from hospital three days post-surgery. On follow up eight days and 12 days post-circumcision, they remained free of complications. Conclusion Circumcision can be safely performed in boys with mild Hemophilia A following adequate pre-operative planning and prophylactic therapy. A standardised protocol for the Yogyakarta Bleeding Disorders Program. evolving from this experience, is being planned.